O papel do Terceiro Setor na prote????o da pessoa com defici??ncia visual e efetiva????o dos direitos fundamentais no ordenamento jur??dico brasileiro - Oliveira, Ol??via Danielle Mendes de (2017)
The present dissertation analyzes how the actions of the Third Sector organizations are important to provide accessibility to the visually impaired person with regard to the rights that are fundamental to them. The first chapter introduces the legal concept of disabled people and their types in order to provide a better understanding of who can be considered. It also deals with the role played by the State, society and family in relation to the treatment they are given to the disabled and their role in defending their interests. The second chapter is devoted to accessibility and fundamental rights for people with disabilities, given that accessibility is the gateway to freedom and autonomy for the enjoyment of a dignified and egalitarian life. The third chapter presents the concept of the Third Sector and the way in which it has been developing its activities in the provision of the public services that it performs, whose social function has been important for the target public. In the fourth chapter, a study directed to the assistance that the Third Sector has been rendering to the visually impaired person has been carried out, in the supporting role that it exercises in relation to the State. In addition to the legal research, a case study was conducted, with a questionnaire applied to the visually impaired who presented their demands and their perception regarding the Third Sector. Then the final considerations.